Gender Interactions within Hierarchies: Evidence from the Political Arena - Gagliarducci, S.; Paserman, M. D. (Review of Economic Studies, 2012)
This paper studies gender interactions within hierarchical organizations using a large data set on the duration of Italian municipal governments elected between 1993 and 2003. A municipal government can be viewed as a hierarchy, whose stability over time depends on the degree of cooperation between and within ranks. We find that in municipalities headed by female mayors, the probability of early termination of the legislature is higher. This result persists and becomes stronger when we control for municipality fixed effects as well as for non-random sorting of women into municipalities using regression discontinuity in gender-mixed electoral races decided by a narrow margin. The likelihood that a female mayor survives until the end of her term is lowest when the council is entirely male and in regions with less favourable attitudes towards working women. This evidence is suggestive that group dynamics are an important factor in driving the gender difference. Other interpretations receive less support in the data. Our results may provide an alternative explanation for the underrepresentation of women in leadership positions.